Putrajaya Lakes management : sensitivity and conservation towards sustainable community / Wan Noor Anira Wan Ali @ Yaacob, Marina Abdullah and Nor Izana Shobri - Wan Ali @ Yaacob, Wan Noor Anira; Abdullah, Marina; Shobri, Nor Izana (2018)
Lakes, natural or man-made, are important water resources for Malaysia. These inland water bodies cover an area of over 10,000 hectares and contain more than 30 billion cubic metres of water. In positive ways, lake managements are maintaining high level of effectiveness within the lake management. Putrajaya Lake is beneficial not just only to the aspect of water quality and quantity but also as a medium for education resource for the society. Putrajaya Lake is an important destination for recreation, sports and tourism in the country. Additionally, it provides a scenic and self-sustaining ecosystem. Putrajaya Lake has become an important filtering system that treats pollutants and storm water run-off before draining water into the Putrajaya Lake. The urban water body system with a total surface area of 400 hectares was designed and built so as to encircle the core island creating a complex morphometry. The design of the Putrajaya Wetland and Lake has taken into consideration of this hydrological impact. However, the rapid development and many activities surrounding Putrajaya Lake has significant effects on the quality of the water body. Therefore, the purpose of this study was to carry out the Putrajaya lake management towards sensitivity and conservation towards sustainable community. The research methodology was based on two (2) facets which is facet that included site inventory data collection, primary and secondary data. The second facet analysed the site analysis that included (i) water quality (ii) lake ecosystem and (iii) monitoring the activities at Putrajaya Lake. The findings were used in to assist Putrajaya Lake to improve its management and to have a better strategic plan and formulation of a long term lakes catchment development and management plan. This will help Putrajaya to achieve its inspiration of “City in a Garden”. Besides, development of an integrated system of lake management that will ensure sustainability of community and ecosystems.